High-angle light diffusion plate and method for manufacturing the same

CN122984104APending Publication Date: 2026-10-27JIANGXI SHENGHUI OPTICAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611282639.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0014]本发明的有益效果:利用材料配比和膜面结构,在提高扩散板光通量和匀光性的同时,可以提高眼睛舒适度并预防近视。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a high-ambient light diffusion plate and a preparation method thereof, and belongs to the technical field of high-performance optical diffusion plates. The material and structure of the diffusion plate are special, the light path transmission is redesigned, part of the imaging light can be scattered and converted into ambient light, clear visual effects are ensured, and the diffusion plate is eye-friendly. The high-ambient light diffusion plate prepared by the application has clear and regular double-sided lines, and has excellent light diffusion performance, mechanical performance and weather resistance, and meets the high-end use standard of the high-ambient light diffusion plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-performance optical diffuser technology, and in particular to a high-resolution optical diffuser and its preparation method. Background Technology

[0002] In recent years, the incidence of myopia has increased significantly globally, especially in Asia. Traditional lighting design focuses on "brightness" and "color accuracy," but has significant blind spots: it only considers the total amount of light, not the direction of the light source; it only focuses on color perception, not the biological effects of the spectrum; it only focuses on color reproduction, not the retinal signals. The high-ambient-light theory proposes that the key to myopia prevention lies in the proportion of ambient light. The higher the proportion of ambient light, the better for the eyes. For example, outdoors: 80% ambient light, 20% imaging light; indoors: 20% ambient light, 80% imaging light. Therefore, providing a high-ambient-light diffuser plate and its preparation method, which converts part of the imaging light scattering into ambient light, ensuring clear visual effects and being eye-friendly, is of great significance. Summary of the Invention

[0003] The purpose of this invention is to provide a high-resolution light diffusion plate and its preparation method to solve the above-mentioned technical problems.

[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution: The present invention provides a high-resolution light diffusion plate, which is prepared from the following raw materials in parts by weight: 10-20 parts of styrene-maleic anhydride alternating copolymer composite microspheres; 35-45 parts of matrix resin masterbatch; 10-15 parts of amide-hybrid polyester; 5-10 parts of polymethyl methacrylate modified product; 1-3 parts glass microspheres; 3-5 parts of silicon dioxide; 3-5 parts of titanium dioxide; 8-10 parts of organosilicon modifier; The components and their mass fractions in the matrix resin masterbatch are as follows: 15-20 parts polycarbonate, 10-15 parts polystyrene, and 5-10 parts polyethylene terephthalate-1,4-cyclohexanediol ester.

[0005] Furthermore, the particle size of the styrene-maleic anhydride alternating copolymer composite microspheres is 80~150nm; The polycarbonate is an aromatic polycarbonate with a melt index of 8~10g / 10min.

[0006] Furthermore, the amide unit content of the amide hybrid polyester is 4-6 mol%, and the amide hybrid polyester is a polyester modified with hexamethylenediamine or decanediamine.

[0007] Furthermore, the refractive index of the polymethyl methacrylate modified material is ≥1.5; The glass microspheres are solid glass microspheres with a particle size of ≥800 mesh and a refractive index of ≥2.2; The silica is fumed silica with a particle size ≤50nm.

[0008] Furthermore, the surface of the titanium dioxide is treated with a silane coupling agent, and the particle size of the titanium dioxide is ≤100nm; The silane coupling agent includes one or more of 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-methacryloyloxypropyltrimethoxysilane, and the organosilicon modifier includes one or more of organosilicon-modified PMMA and organosilicon-modified SMA.

[0009] Furthermore, the surface structure of the high-resolution light diffusion plate is a hexagonal mesh on one side and a hexagonal pyramidal structure on the other side; The hexagonal mesh has a mesh density of 2300~2700 meshes, and the unit arrangement density of the hexagonal pyramid structure is 800~1200 meshes.

[0010] The present invention also provides a method for preparing the above-mentioned high-resolution light diffusion plate, comprising the following steps: Step 1) Mix the raw materials according to the mass ratio and then extrude them into a twin-screw extruder; Step 2) The material extruded in Step 1) is rolled and cooled by a pressure roller with engraved surface to obtain a high-resolution light diffusion plate.

[0011] Furthermore, in step 1), the extrusion temperature is 260~300℃.

[0012] Furthermore, in step 2), the temperature of the pressure roller is 80~120℃, and the temperature of the cooling roller is ≤30℃.

[0013] Furthermore, in step 2), the thickness of the obtained high-resolution light diffusion plate is 60~2000μm and the width is ≤1200mm.

[0014] The beneficial effects of this invention are: by utilizing the material ratio and film structure, while improving the light flux and uniformity of the diffuser plate, it can also improve eye comfort and prevent myopia. Detailed Implementation

[0015] The present invention provides a high-resolution light diffusion plate, which is prepared from the following raw materials in parts by weight: 10-20 parts of styrene-maleic anhydride alternating copolymer composite microspheres; 35-45 parts of matrix resin masterbatch; 10-15 parts of amide-hybrid polyester; 5-10 parts of polymethyl methacrylate modified product; 1-3 parts glass microspheres; 3-5 parts of silicon dioxide; 3-5 parts of titanium dioxide; 8-10 parts of organosilicon modifier; The components and their mass fractions in the matrix resin masterbatch are as follows: 15-20 parts polycarbonate, 10-15 parts polystyrene, and 5-10 parts polyethylene terephthalate-1,4-cyclohexanediol ester.

[0016] In this invention, the amount of the styrene-maleic anhydride alternating copolymer composite microspheres added is preferably 12 to 18 parts by mass, and more preferably 15 parts.

[0017] In this invention, the styrene-maleic anhydride alternating copolymer composite microspheres are SMA microspheres with stable alternating structure and uniform particle size prepared by self-stabilizing precipitation polymerization.

[0018] In this invention, the amount of the matrix resin masterbatch added is preferably 38 to 42 parts by weight, and more preferably 40 parts.

[0019] In this invention, the amount of the amide hybrid polyester added is preferably 13 parts by weight.

[0020] In this invention, the amide hybrid polyester is obtained by copolymerizing hexamethylenediamine and decanediamine with terephthalic acid instead of ethylene glycol. The glass transition temperature is above 82°C, the intrinsic viscosity is above 7.8, and the amide unit content is 4-6 mol.

[0021] In this invention, the amount of the polymethyl methacrylate modifier added is preferably 8 parts by weight.

[0022] In this invention, the glass transition temperature of the polymethyl methacrylate modified material is 55-90℃, the number average molecular weight is 15,000-30,000, the molecular weight distribution is 1.5-5.0, and the refractive index is 1.46-1.60.

[0023] In this invention, the preferred amount of glass microspheres added is 2 parts by weight.

[0024] In this invention, the amount of silicon dioxide added is preferably 4 parts by weight.

[0025] In this invention, the amount of titanium dioxide added is preferably 4 parts by weight.

[0026] In this invention, the amount of the organosilicon modifier added is preferably 9 parts by weight.

[0027] In this invention, the amount of polycarbonate added to the matrix resin masterbatch is preferably 18 parts by weight.

[0028] In this invention, the amount of polystyrene added to the matrix resin masterbatch is preferably 13 parts by weight.

[0029] In this invention, the amount of polyethylene terephthalate-1,4-cyclohexanediol ester added to the matrix resin masterbatch is preferably 8 parts by weight.

[0030] In this invention, the particle size of the styrene-maleic anhydride alternating copolymer composite microspheres is 80-150 nm, preferably 100-120 nm; The polycarbonate is an aromatic polycarbonate with a melt index of 8-10 g / 10 min, preferably 9 g / 10 min.

[0031] In this invention, the amide unit content of the amide hybrid polyester is 4-6 mol%, preferably 5 mol%; the amide hybrid polyester is a polyester modified with hexamethylenediamine or decanediamine, preferably a hexamethylenediamine-modified polyester.

[0032] In this invention, the refractive index of the polymethyl methacrylate modified material is ≥1.5, preferably >1.5; The glass microspheres are solid glass microspheres with a particle size of ≥800 mesh and a refractive index of ≥2.2, preferably >2.2; The silica is fumed silica with a particle size ≤50nm, preferably ≤40nm.

[0033] In this invention, the surface of the titanium dioxide is treated with a silane coupling agent, and the particle size of the titanium dioxide is ≤100nm, preferably <100nm, and more preferably ≤80nm.

[0034] In this invention, the organosilicon modifier has good impact strength and flexibility, and can withstand high temperatures of 120°C and low temperatures of -60°C.

[0035] In this invention, the surface structure of the high-resolution light diffusion plate is a hexagonal mesh on one side and a hexagonal pyramid structure on the other side; The hexagonal mesh has a mesh density of 2300-2700 mesh, preferably 2500 mesh; the unit arrangement density of the hexagonal pyramid structure is 800-1200 mesh, preferably 1000 mesh.

[0036] The present invention also provides a method for preparing the above-mentioned high-resolution light diffusion plate, comprising the following steps: Step 1) Mix the raw materials according to the mass ratio and then extrude them into a twin-screw extruder; Step 2) The material extruded in Step 1) is rolled and cooled by a pressure roller with engraved surface to obtain a high-resolution light diffusion plate.

[0037] In this invention, in step 1), the extrusion temperature is 260~300℃, preferably 280℃.

[0038] In this invention, in step 2), the temperature of the pressure roller is 80~120℃, preferably 100℃; the temperature of the cooling roller is ≤30℃, preferably ≤20℃.

[0039] In this invention, in step 2), the thickness of the obtained high-resolution light diffusion plate is 60~2000μm, preferably 100~1500μm; the width is ≤1200mm, preferably ≤1000mm.

[0040] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0041] Example 1

[0042] Raw material system: Polycarbonate (melt index 9 g / 10 min): 20 parts Polystyrene: 15 parts Polyethylene terephthalate-1,4-cyclohexanediol ester: 10 parts Sebacdiamine-modified amide hybrid polyester (amide unit content 5 mol%): 10 parts Polymethyl methacrylate modified (refractive index 1.52): 10 parts Styrene-maleic anhydride alternating copolymer composite microspheres: 20 parts Solid glass microspheres (1000 mesh, refractive index 2.25): 1 part Fumed silica (40nm particle size): 3 parts Silane coupling agent modified titanium dioxide (particle size 80nm): 3 parts High and low temperature resistant silicone modifier: 8 parts; The above materials were put into a high-speed mixer and stirred at room temperature and speed of 800 r / min for 15 minutes to ensure that all powders, microspheres and resin matrix were uniformly dispersed without agglomeration and clumping, so as to obtain a uniform mixture. The resulting mixture is fed into a twin-screw extruder, and the processing temperature is controlled in stages at 260℃, 275℃, 285℃, 290℃, and 295℃, the die head temperature is 300℃, and the screw speed is 300r / min to ensure that the material is fully plasticized, mixed evenly, and extruded and melted to produce masterbatch. The obtained masterbatch is fed into the calendering unit, and the surface is formed by using customized textured rollers. The roller temperature is controlled at 100℃. Through precise pressing by the rollers, a 2500-mesh hexagonal mesh is formed on one side of the board and a 1000-mesh hexagonal pyramidal microstructure is formed on the other side. The obtained board was cut into wide-format high-resolution light diffusion boards with a thickness of 1500μm and a maximum width of 1200mm, with clear and regular patterns on both sides.

[0043] Example 2

[0044] Raw material system: Polycarbonate (melt index 9g / 10min): 10 parts Polystyrene: 10 parts Polyethylene terephthalate-1,4-cyclohexanediol ester: 10 parts Sebacdiamine-modified amide hybrid polyester (amide unit content 5 mol%): 15 parts Polymethyl methacrylate modified (refractive index 1.52): 10 parts Styrene-maleic anhydride alternating copolymer composite microspheres: 20 parts Solid glass microspheres (1000 mesh, refractive index 2.25): 2 parts Fumed silica (40nm particle size): 3 parts Silane coupling agent modified titanium dioxide (particle size 80nm): 3 parts High and low temperature resistant silicone modifier: 8 parts; The above materials were put into a high-speed mixer and stirred at room temperature and speed of 800 r / min for 15 minutes to ensure that all powders, microspheres and resin matrix were uniformly dispersed without agglomeration and clumping, so as to obtain a uniform mixture. The resulting mixture is fed into a twin-screw extruder, and the processing temperature is controlled in stages at 260℃, 275℃, 285℃, 290℃, and 295℃, the die head temperature is 300℃, and the screw speed is 300r / min to ensure that the material is fully plasticized, mixed evenly, and extruded and melted to produce masterbatch. The obtained masterbatch is fed into the calendering unit, and the surface is formed by using customized textured rollers. The roller temperature is controlled at 100℃. Through precise pressing by the rollers, a 2500-mesh hexagonal mesh is formed on one side of the board and a 1000-mesh hexagonal pyramidal microstructure is formed on the other side. The obtained board was cut into wide-format high-resolution light diffusion boards with a thickness of 1500μm and a maximum width of 1200mm, with clear and regular patterns on both sides.

[0045] Example 3

[0046] Raw material system: Polycarbonate (melt index 9g / 10min): 10 parts Polystyrene: 10 parts Polyethylene terephthalate-1,4-cyclohexanediol ester: 10 parts Sebacdiamine-modified amide hybrid polyester (amide unit content 5 mol%): 15 parts Polymethyl methacrylate modified (refractive index 1.52): 10 parts Styrene-maleic anhydride alternating copolymer composite microspheres: 20 parts Solid glass microspheres (1000 mesh, refractive index 2.25): 1 part Fumed silica (40nm particle size): 3 parts Silane coupling agent modified titanium dioxide (particle size 80nm): 3 parts High and low temperature resistant silicone modifier: 8 parts; The above materials were put into a high-speed mixer and stirred at room temperature and speed of 800 r / min for 15 minutes to ensure that all powders, microspheres and resin matrix were uniformly dispersed without agglomeration and clumping, so as to obtain a uniform mixture. The resulting mixture is fed into a twin-screw extruder, and the processing temperature is controlled in stages at 260℃, 275℃, 285℃, 290℃, and 295℃, the die head temperature is 300℃, and the screw speed is 300r / min to ensure that the material is fully plasticized, mixed evenly, and extruded and melted to produce masterbatch. The obtained masterbatch is fed into the calendering unit, and the surface is formed by using customized textured rollers. The roller temperature is controlled at 100℃. Through precise pressing by the rollers, a 2500-mesh hexagonal mesh is formed on one side of the board and a 1000-mesh hexagonal pyramidal microstructure is formed on the other side. The obtained board was cut into wide-format high-resolution light diffusion boards with a thickness of 1500μm and a maximum width of 1200mm, with clear and regular patterns on both sides.

[0047] Example 4

[0048] Raw material system: Polycarbonate (melt index 9g / 10min): 10 parts Polystyrene: 10 parts Polyethylene terephthalate-1,4-cyclohexanediol ester: 10 parts Sebacdiamine-modified amide hybrid polyester (amide unit content 5 mol%): 15 parts Polymethyl methacrylate modified (refractive index 1.52): 5 parts Styrene-maleic anhydride alternating copolymer composite microspheres: 20 parts Solid glass microspheres (1000 mesh, refractive index 2.25): 1 part Fumed silica (40nm particle size): 3 parts Silane coupling agent modified titanium dioxide (particle size 80nm): 3 parts High and low temperature resistant silicone modifier: 8 parts; The above materials were put into a high-speed mixer and stirred at room temperature and speed of 800 r / min for 15 minutes to ensure that all powders, microspheres and resin matrix were uniformly dispersed without agglomeration and clumping, so as to obtain a uniform mixture. The resulting mixture is fed into a twin-screw extruder, and the processing temperature is controlled in stages at 260℃, 275℃, 285℃, 290℃, and 295℃, the die head temperature is 300℃, and the screw speed is 300r / min to ensure that the material is fully plasticized, mixed evenly, and extruded and melted to produce masterbatch. The obtained masterbatch is fed into the calendering unit, and the surface is formed by using customized textured rollers. The roller temperature is controlled at 100℃. Through precise pressing by the rollers, a 2500-mesh hexagonal mesh is formed on one side of the board and a 1000-mesh hexagonal pyramidal microstructure is formed on the other side. The obtained board was cut into wide-format high-resolution light diffusion boards with a thickness of 1500μm and a maximum width of 1200mm, with clear and regular patterns on both sides.

[0049] Example 5

[0050] Raw material system: Polycarbonate (melt index 9g / 10min): 10 parts Polystyrene: 10 parts Polyethylene terephthalate-1,4-cyclohexanediol ester: 10 parts Sebacdiamine-modified amide hybrid polyester (amide unit content 5 mol%): 15 parts Polymethyl methacrylate modified (refractive index 1.52): 8 parts Styrene-maleic anhydride alternating copolymer composite microspheres: 20 parts Solid glass microspheres (1000 mesh, refractive index 2.25): 1 part Fumed silica (40nm particle size): 3 parts Silane coupling agent modified titanium dioxide (particle size 80nm): 3 parts High and low temperature resistant silicone modifier: 8 parts; The above materials were put into a high-speed mixer and stirred at room temperature and speed of 800 r / min for 15 minutes to ensure that all powders, microspheres and resin matrix were uniformly dispersed without agglomeration and clumping, so as to obtain a uniform mixture. The resulting mixture is fed into a twin-screw extruder, and the processing temperature is controlled in stages at 260℃, 275℃, 285℃, 290℃, and 295℃, the die head temperature is 300℃, and the screw speed is 300r / min to ensure that the material is fully plasticized, mixed evenly, and extruded and melted to produce masterbatch. The obtained masterbatch is fed into the calendering unit, and the surface is formed by using customized textured rollers. The roller temperature is controlled at 100℃. Through precise pressing by the rollers, a 2500-mesh hexagonal mesh is formed on one side of the board and a 1000-mesh hexagonal pyramidal microstructure is formed on the other side. The obtained board was cut into wide-format high-resolution light diffusion boards with a thickness of 1500μm and a maximum width of 1200mm, with clear and regular patterns on both sides.

[0051] Example 6

[0052] Raw material system: Polycarbonate (melt index 9 g / 10 min): 20 parts Polystyrene: 15 parts Polyethylene terephthalate-1,4-cyclohexanediol ester: 10 parts Sebacdiamine-modified amide hybrid polyester (amide unit content 5 mol%): 10 parts Polymethyl methacrylate modified (refractive index 1.52): 10 parts Styrene-maleic anhydride alternating copolymer composite microspheres: 20 parts Solid glass microspheres (1000 mesh, refractive index 2.25): 1 part Fumed silica (particle size 40nm): 5 parts Silane coupling agent modified titanium dioxide (particle size 80nm): 5 parts High and low temperature resistant silicone modifier: 8 parts; The above materials were put into a high-speed mixer and stirred at room temperature and speed of 800 r / min for 15 minutes to ensure that all powders, microspheres and resin matrix were uniformly dispersed without agglomeration and clumping, so as to obtain a uniform mixture. The resulting mixture is fed into a twin-screw extruder, and the processing temperature is controlled in stages at 260℃, 275℃, 285℃, 290℃, and 295℃, the die head temperature is 300℃, and the screw speed is 300r / min to ensure that the material is fully plasticized, mixed evenly, and extruded and melted to produce masterbatch. The obtained masterbatch is fed into the calendering unit, and the surface is formed by using customized textured rollers. The roller temperature is controlled at 100℃. Through precise pressing by the rollers, a 2500-mesh hexagonal mesh is formed on one side of the board and a 1000-mesh hexagonal pyramidal microstructure is formed on the other side. The obtained board was cut into wide-format high-resolution light diffusion boards with a thickness of 1500μm and a maximum width of 1200mm, with clear and regular patterns on both sides.

[0053] Comparative Example 1

[0054] Raw material system: Polycarbonate (melt index 9 g / 10 min): 20 parts Polystyrene: 15 parts Polyethylene terephthalate-1,4-cyclohexanediol ester: 10 parts Sebacdiamine-modified amide hybrid polyester (amide unit content 5 mol%): 10 parts Polymethyl methacrylate modified (refractive index 1.52): 10 parts Styrene-maleic anhydride alternating copolymer composite microspheres: 20 parts Solid glass microspheres (1000 mesh, refractive index 2.25): 1 part Fumed silica (40nm particle size): 3 parts Silane coupling agent modified titanium dioxide (particle size 80nm): 3 parts High and low temperature resistant silicone modifier: 8 parts; The above materials were put into a high-speed mixer and stirred at room temperature and speed of 800 r / min for 15 minutes to ensure that all powders, microspheres and resin matrix were uniformly dispersed without agglomeration and clumping, so as to obtain a uniform mixture. The resulting mixture is fed into a twin-screw extruder, and the processing temperature is controlled in stages at 260℃, 275℃, 285℃, 290℃, and 295℃, the die head temperature is 300℃, and the screw speed is 300r / min to ensure that the material is fully plasticized, mixed evenly, and extruded and melted to produce masterbatch. The obtained masterbatch is fed into a calendering unit, where a custom textured roller is used for surface forming. The roller temperature is controlled at 100°C. Through precise pressing by the roller, the film surface is structureless. The obtained board was cut into wide-format high-resolution light diffusion boards with a thickness of 1500μm and a maximum width of 1200mm, with clear and regular patterns on both sides.

[0055] Comparative Example 2

[0056] Raw material system: Polycarbonate (melt index 9 g / 10 min): 20 parts Polystyrene: 15 parts Polyethylene terephthalate-1,4-cyclohexanediol ester: 10 parts Sebacdiamine-modified amide hybrid polyester (amide unit content 5 mol%): 10 parts Solid glass microspheres (1000 mesh, refractive index 2.25): 1 part Fumed silica (40nm particle size): 3 parts Silane coupling agent modified titanium dioxide (particle size 80nm): 3 parts High and low temperature resistant silicone modifier: 8 parts; The above materials were put into a high-speed mixer and stirred at room temperature and speed of 800 r / min for 15 minutes to ensure that all powders, microspheres and resin matrix were uniformly dispersed without agglomeration and clumping, so as to obtain a uniform mixture. The resulting mixture is fed into a twin-screw extruder, and the processing temperature is controlled in stages at 260℃, 275℃, 285℃, 290℃, and 295℃, the die head temperature is 300℃, and the screw speed is 300r / min to ensure that the material is fully plasticized, mixed evenly, and extruded and melted to produce masterbatch. The obtained masterbatch is fed into the calendering unit, and the surface is formed by using customized textured rollers. The roller temperature is controlled at 100℃. Through precise pressing by the rollers, a 2500-mesh hexagonal mesh is formed on one side of the board and a 1000-mesh hexagonal pyramidal microstructure is formed on the other side. The obtained board was cut into wide-format high-resolution light diffusion boards with a thickness of 1500μm and a maximum width of 1200mm, with clear and regular patterns on both sides.

[0057] Comparative Example 3

[0058] Raw material system: Polycarbonate (melt index 9 g / 10 min): 20 parts Polystyrene: 15 parts Polyethylene terephthalate-1,4-cyclohexanediol ester: 10 parts Polymethyl methacrylate modified (refractive index 1.52): 10 parts Styrene-maleic anhydride alternating copolymer composite microspheres: 20 parts Solid glass microspheres (1000 mesh, refractive index 2.25): 1 part Fumed silica (40nm particle size): 3 parts Silane coupling agent modified titanium dioxide (particle size 80nm): 3 parts The above materials were put into a high-speed mixer and stirred at room temperature and speed of 800 r / min for 15 minutes to ensure that all powders, microspheres and resin matrix were uniformly dispersed without agglomeration and clumping, so as to obtain a uniform mixture. The resulting mixture is fed into a twin-screw extruder, and the processing temperature is controlled in stages at 260℃, 275℃, 285℃, 290℃, and 295℃, the die head temperature is 300℃, and the screw speed is 300r / min to ensure that the material is fully plasticized, mixed evenly, and extruded and melted to produce masterbatch. The obtained masterbatch is fed into the calendering unit, and the surface is formed by using customized textured rollers. The roller temperature is controlled at 100℃. Through precise pressing by the rollers, a 2500-mesh hexagonal mesh is formed on one side of the board and a 1000-mesh hexagonal pyramidal microstructure is formed on the other side. The obtained board was cut into wide-format high-resolution light diffusion boards with a thickness of 1500μm and a maximum width of 1200mm, with clear and regular patterns on both sides.

[0059] Performance testing

[0060] Table 1. Performance test data characterization of the samples obtained in Examples 1-6 and Comparative Examples 1-3

[0061] As can be seen from the above embodiments, the present invention provides a high-ambient-light diffuser plate and its preparation method. The diffuser plate has special materials and structure, and the optical path transmission is redesigned to convert some of the imaging light scattering into ambient light, ensuring a clear visual effect and being eye-friendly.

[0062] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A high-resolution light diffuser plate, characterized in that, It is prepared from raw materials comprising the following parts by mass: 10-20 parts of styrene-maleic anhydride alternating copolymer composite microspheres; 35-45 parts of matrix resin masterbatch; 10-15 parts of amide-hybrid polyester; 5-10 parts of polymethyl methacrylate modified product; 1-3 parts glass microspheres; 3-5 parts of silicon dioxide; 3-5 parts of titanium dioxide; 8-10 parts of organosilicon modifier; The components and their mass fractions in the matrix resin masterbatch are as follows: 15-20 parts polycarbonate, 10-15 parts polystyrene, and 5-10 parts polyethylene terephthalate-1,4-cyclohexanediol ester.

2. The high-resolution light diffuser plate according to claim 1, characterized in that, The particle size of the styrene-maleic anhydride alternating copolymer composite microspheres is 80~150nm; The polycarbonate is an aromatic polycarbonate with a melt index of 8~10g / 10min.

3. The high-resolution light diffuser plate according to claim 1, characterized in that, The amide hybrid polyester has an amide unit content of 4-6 mol%, and the amide hybrid polyester is a polyester modified with hexamethylenediamine or decanediamine.

4. The high-resolution light diffusion plate according to claim 2 or 3, characterized in that, The refractive index of the polymethyl methacrylate modified material is ≥1.5; The glass microspheres are solid glass microspheres with a particle size of ≥800 mesh and a refractive index of ≥2.2; The silica is fumed silica with a particle size ≤50nm.

5. The high-resolution light diffuser plate according to claim 4, characterized in that, The surface of the titanium dioxide is treated with a silane coupling agent, and the particle size of the titanium dioxide is ≤100nm; The silane coupling agent includes one or more of 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-methacryloyloxypropyltrimethoxysilane, and the organosilicon modifier includes one or more of organosilicon-modified PMMA and organosilicon-modified SMA.

6. The high-resolution light diffuser plate according to claim 1, characterized in that, The surface structure of the high-resolution light diffusion plate is a hexagonal mesh on one side and a hexagonal pyramid structure on the other side; The hexagonal mesh has a mesh density of 2300~2700 meshes, and the unit arrangement density of the hexagonal pyramid structure is 800~1200 meshes.

7. The method for preparing the high-resolution light diffusion plate according to any one of claims 1 to 6, characterized in that, Includes the following steps: Step 1) Mix the raw materials according to the mass ratio and then extrude them into a twin-screw extruder; Step 2) The material extruded in Step 1) is rolled and cooled by a pressure roller with engraved surface to obtain a high-resolution light diffusion plate.

8. The method for preparing a high-resolution light diffusion plate according to claim 7, characterized in that, In step 1), the extrusion temperature is 260~300℃.

9. The method for preparing a high-resolution light diffuser plate according to claim 8, characterized in that, In step 2), the temperature of the pressure roller is 80~120℃, and the temperature of the cooling roller is ≤30℃.

10. The method for preparing a high-resolution light diffusion plate according to claim 8 or 9, characterized in that, In step 2), the thickness of the obtained high-resolution light diffusion plate is 60~2000μm and the width is ≤1200mm.